2022
DOI: 10.1021/acssuschemeng.2c01257
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing Essential Oil Components through Cocrystallization: Sustainable and Smart Materials for Food Preservation and Agricultural Applications

Abstract: The ever-increasing attention on environmental problems and sustainability has highlighted several problems related to the use of conventional pesticides in the agricultural industry, e.g., toxic residues in the soil and hazards to the environment and human health. In the search for natural antimicrobial and insecticide alternatives, essential oils (EOs) and their active components have emerged as promising candidates, but they suffer from some drawbacks related to their physical properties. We exploited cocry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Additionally, bioassay assays demonstrated that the cocrystals maintained their potent activity without any significant loss. More recently, an extended investigation focused on the design of nine additional cocrystals specifically targeting CAR and THY with the primary aim of achieving prolonged release characteristics . Notably, these newly developed EO cocrystals showcased remarkable effectiveness in extending the shelf life of fruits stored at room temperature .…”
Section: Application Scenarios Of Solid-state Formsmentioning
confidence: 99%
“…Additionally, bioassay assays demonstrated that the cocrystals maintained their potent activity without any significant loss. More recently, an extended investigation focused on the design of nine additional cocrystals specifically targeting CAR and THY with the primary aim of achieving prolonged release characteristics . Notably, these newly developed EO cocrystals showcased remarkable effectiveness in extending the shelf life of fruits stored at room temperature .…”
Section: Application Scenarios Of Solid-state Formsmentioning
confidence: 99%
“…For example, the limited application of essential oils due to the high volatility and scarce water solubility was expanded using cocrystal engineering. 30,31 For highly water-soluble herbicides, however, the cocrystal strategy has not been applied to manage the release and leaching behaviour in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Metamitron (MET), a predominant member of the triazinone class, is a classic, highly water-soluble herbicide widely used for the control of broad-leaved weeds and grasses in sugar beet and flower bulb cultures. 31 As a pre-and post-emergence selective herbicide, it exerts a herbicidal impact by blocking the photosynthetic Hill reaction when absorbed primarily by plant roots and then transferred to leaves. 32,33 Due to its rapid inactivation by N-deamination in sugar beets, MET is highly selective to weeds in sugar beet fields and is currently sold in more than 25 countries globally.…”
Section: Introductionmentioning
confidence: 99%
“…30,34,35 The delivery profile of essential oils could also be modified by cocrystallization. 36 More interestingly, the molecular selfassembly varied in different cocrystals, leading to a complex supramolecular architecture. 37−41 The various assembly is driven by supramolecular recognition, and synthons are often employed to describe the non-covalent interactions between structural motifs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The cocrystallization technique brings diversified solid-state forms for APIs, including those lacking ionizable functional groups . Therefore, it has been adopted as an effective approach to improve the physiochemical properties of target compounds. For example, the cocrystals of liquid materials could be transformed into a solid state with elevated melting points. ,, The delivery profile of essential oils could also be modified by cocrystallization . More interestingly, the molecular self-assembly varied in different cocrystals, leading to a complex supramolecular architecture. The various assembly is driven by supramolecular recognition, and synthons are often employed to describe the non-covalent interactions between structural motifs. , In our previous work, a series of stable vitamin D cocrystals were synthesized, which were formed by the hydrogen-bonding interactions between hydroxyl groups on the A-ring of the steroid nucleus. , We further assumed that the same interaction is not limited to steroids and the supramolecular synthon could be simplified as the hydrogen bonds between cyclohexanol structural motifs.…”
Section: Introductionmentioning
confidence: 99%